Role of genotyping in prediction of disseminated intravascular coagulation and multiple organ failure in children with generalized forms of meningococcal infection - S. I. Kapustin; A. A. Vilnits; Zh. Yu. Sidorova; V. N. Chebotkevich; L. P. Papayan; L. A. Alekseeva; N. V. Skripchenko; S. S. Bessmeltsev (Журнал инфектологии, 2019)
Aim: To investigate the features of allelic polymorphism, of several immune- and hemostasis-related genes in children with generalized, meningococcal infections and. to assess the usefulness of genotyping for prediction, of severe disseminated intravascular coagulation (DIC) and. multiple organ dysfunction, syndrome in these patients.Materials and methods: we studied. 20 children aged, from 8 months up to 17 years with generalized, meningococcal infections who developed DIC or/and multiple organ dysfunction syndrome. The control group consisted, of 200 blood, donors. Genomic DNA was isolated, from peripheral blood, leucocytes. Allelic variants of genes coding for plasma hemostatic factors (FI-A, FI-B, FXIII-A, PAI-1, ТРА) or pro-inflammatory cytokines (IL-6, IL-1B, TNF-A) were detected by PCR and. subsequent restriction, analysis. Allele and. genotype frequencies were calculated, by direct counting, and. their differences between the groups were assessed, by Fisher's exact test. For statistical analysis, the GraphPad. Prism, ver.4.0 software was used.Results: in the group of children with generalized, meningococcal infections, the frequency of heterozygotes for the IL-6 -174 G/C polymorphism, was 1.5-fold higher than in the controls (75.0% vs. 50.0%, respectively, OR=3.0; 95% CI: 1.1-8.6; p=0.037). Genotype TPA Del/Del was detected 4-fold more frequently in children who developed multiple organ dysfunction syndrome than in those with the more favorable disease course (45.4% vs. 11.1%, respectively, OR=6.7; 95% CI: 0.6-73.1; p=0.16). Moreover, among the patients having multiple organ dysfunction, syndrome, we observed, more frequently individuals who possessed, at least 2 unfavorable genetic variants (p=0.022).Conclusion: Simultaneous assessment of nucleotide variations in 8 studied genes could help to define the group of children with high, risk of multiple organ dysfunction, syn-drome.Genotype TPA Del/Del, associated, with decreased, production, of this factor, might serve as a marker of unfavorable DIC course and possible predictor of multiple organ dysfunction. syndrome in children with generalized, meningpcoc-cal infections.